VENTURE ECOSYSTEM IN RUSSIA AND THE UNITED STATES: A COMPARATIVE ANALYSIS - E. N. Dunenkova; E. A. Lysova (Вестник университета)
The aim of the research is to analyse the features of development and current state of the main elements of venture ecosystem in Russia and the United States. To achieve this goal, the authors reveal and analyse the key features of the studied natural ecosystems. The paper considers the chronology of the stages of development of venture ecosystems in both countries, determines their current state, including the volume and number of concluded venture transactions, their ratio by stages of the investment process. The article highlights the key differences between socio-cultural factors and legal frameworks that regulate and influence the activities of venture ecosystems. The study identifies the main problematic aspects of the development of the innovative potential of the Russian Federation and the reasons for their occurrence. The authors carry out a comparative analysis of the venture industry in Russia and the United States, identify on its basis, the key problems that hinder the development of the venture ecosystem in Russia, and give recommendations for overcoming.